Aqueous extract of Tamarindus indica fruit pulp exhibits antihyperglycaemic activity - Rajesh Nivesh Krishna; Anitha Roy; Devaraj Ezhilarasan (Mashhad University of Medical Sciences, 2020)
Objective: Tamarindus indica Linn.(T.indica) is a well-known plant used in traditional medicine. The plant is popular for its antidiabetic activity. However, effect so f its aqueous fruit pulp extract on carbohydrate hydrolyzing enzymes and its glucose uptake potential were not explored. Materials and Methods: The antidiabetic activity was assessed by in-vitro α-amylase and α-glucosidase inhibitory assays after preliminary phytochemical analysis. MTT assay was carried out to find cytotoxicity. Glucose uptake activity of the extract was carried out using L6 myotubes. Results:The results showed a strong α-amylase inhibitory activity for the fruit pulp extract of T.indica compared to standard acarbose; the IC50 of the fruit pulp extract of T.indica and acarbose was 34.19 µg/ml 34.83µM. The extract also showed moderate α-glucosidase inhibitory activity. IC50 of the fruit pulp extract of T.indica and acarbose were 56.91µg/ml and 45.69µM respectively. The cytotoxicity assay showed IC50 of >300µg/ml and ≥1000µM for the fruit pulp extract of T.indica     and metformin. The extract showed 63.99±0.08% glucose uptake in L6 myotubes whereas metformin and insulin at  10µg/ml and 10µM exhibited an uptake of 76.99±0.3% and 84.48±0.45% glucose, respectively. Conclusion: The study revealed that the fruit pulp extract of T.indica Linn does not show any cytotoxic effect and has very good α-amylase and good α-glucosidase inhibitory activities. The glucose uptake potential proves its postprandial hypoglycemic effect. Hence, it may be considered an antidiabetic agent for control of postprandial hyperglycemia.